Function and Meaning of Japanese Greetings “Tadaima” and “Okaerinasai” on Social Media X: Sociolinguistic Study (LITPAM, 2025)
This study explores the functions and meanings of the Japanese greetings tadaima and okaerinasai as they are used on the social media platform X. Traditionally, these greetings serve specific functions: tadaima is used when someone returns home, and Okaerinasai is used to welcome them back, typically within shared living spaces. However, as language evolves, the context and usage of these greetings have expanded beyond their original meanings, particularly in digital spaces where formal rules of language use are more fluid. The data in this study will be analyzed using qualitative methods and sociolinguistic theories that address shifts in the function and meaning of tadaima and okaerinasai when used by social media users on X. The aim of this study is to examine how these greetings are used on social media platform X, exploring the differences between their traditional and contemporary uses and how these shifts influence their function and meaning in online interactions.